Afforestation of Dry and Desert Areas with a Rainfall of below 30 Inches in the United Provinces
Such tracts are not comprised by the main forest belt of the United Provinces and the only areas falling into this category are the ravine blocks of Etawah, together with a few forest blocks in other western districts. Extensive afforestation operations were carried out between 1914 and 1929 after which (as a result of our experience) the afforestation policy was changed to the present one of restocking such areas by natural means, induced by protection combined with regulation of grazing. The following note by the Divisional Forest Officer, Afforestation Division